Desafios do programa bolsa família no município de Iaçu-BA: possibilidades de transformação na vida das famílias beneficiárias - Carneiro, Daniel Sampaio (2023)
This present master's thesis is a study about the impact of the Bolsa Família Program in the city of Iaçu-BA. The study demonstrates the importance of the Bolsa Família Income Transfer Program, instituted by the Brazilian Social Assistance Policy, to face poverty and extreme poverty, guaranteeing social protection for vulnerable families. The study evidenced the process of institutionalization of social protection, instituted over time and the role of income transfer programs in the government agenda in its different scales until the institutionalization of the Bolsa Família Program. Also, the contemporary challenges for income transfer programs were analyzed. Finally, the impact of the program in IaçuBa was investigated, its importance for the families in social vulnerability and the challenge of establishing a protection network, based on the Municipal Social Assistance Policy, to identify, include and guarantee access to the program for families in social vulnerability. The findings showed the importance of this program for the autonomy of families and for the growth of the municipality. This study also highlighted the challenges of small towns to institute public policies that guarantee transformation in the lives of those who need it most.